The long-term efficacy of tetracycline class antimicrobials as local adjuncts in the treatment of chronic periodontitis: a systematic review and meta-analysis - Soysa, Niroshani S.; Jayakody, Samadhi L.; Alles, C. N. R. A. (Frontiers in Dental Medicine, 2025)
IntroductionThis systematic review assesses the long-term efficacy of tetracycline-class local antimicrobials as adjuncts to scaling and root planing (SRP) in chronic periodontitis. It focuses on improvements in primary outcomes such as probing pocket depth (PPD) and clinical attachment level (CAL), with particular attention to differences in treatment outcomes between smokers and non-smokers. Moreover, the assessed secondary outcomes encompassed bleeding on probing (BOP), gingival index (GI), and plaque index (PI).MethodA systematic search of PubMed, Cochrane Central, Scopus, and Embase identified randomized controlled trials (RCTs) published up to 2024 with ≥6 months follow-up. Long-term efficacy of local tetracyclines was assessed from the selected studies. Meta-analysis calculated weighted mean differences (WMDs) and 95% CIs for the selected periodontal indices using R software. Meta-regression evaluated the impact of study design, assessment approach, treatment phase, and smoking status.ResultsThis systematic review included 52 RCTs assessing the efficacy of adjunctive locally delivered antimicrobials in periodontal therapy. Meta-analysis showed significant benefits in both medium-term (6–9 months) and long-term (12 + months) outcomes. Medium-term results demonstrated significant PPD reduction (WMD 0.516 mm, 95% CI 0.413; 0.620, P = 0.0001) and CAL gain (WMD 0.336 mm, 95% CI 0.204; 0.467, P = 0.0001), while long-term studies showed sustained improvements (PPD: WMD 0.371 mm, 95% CI 0.181; 0.560, P = 0.0001; CAL: WMD 0.310 mm, 95% CI 0.240; 0.381, P = 0.0001). Tetracycline fibers showed the greatest medium-term PPD reduction (0.705 mm), followed by minocycline ointment (0.580 mm). Long-term follow-up also demonstrated significant improvements in BOP, PI, and GI (WMD = 0.1–0.3, P < 0.05). Subgroup analysis revealed non-smokers had greater PPD reduction (0.630 mm vs. 0.112 mm) and CAL gain (0.715 mm vs. 0.464 mm) than smokers (P < 0.05) in long-term. Meta-regression indicated study design influenced outcomes, with split-mouth designs showing significantly greater improvements [β = 0.422, 95% CI (0.231; 0.613), P = 0.0001].DiscussionSustained-release tetracyclines with SRP improve long-term outcomes in chronic periodontitis. Non-smokers exhibit greater clinical gains, though smokers also benefit. These results support tailored adjunctive local tetracycline use to optimize outcomes across patient groups. Further large-scale, long-term RCTs are needed to confirm efficacy and refine delivery formulations.ConclusionLocally delivered tetracycline-class antimicrobials significantly improve periodontal outcomes, with minocycline showing the most consistent benefits. These findings support the integration of tetracycline-class agents into treatment protocols, with special consideration for high-risk patients such as smokers. Future studies should emphasize cost-effectiveness, comparative efficacy, and long-term benefits, including the challenging management of furcation lesions, to better guide clinical decision-making and optimize patient outcomes.